Robust communication in differential relay protection using wireless technique - Badar, Malik Qasim (2015)
The traditional power system protection performance has been constrained by the manufacturers’ specified limit errors of current transformers’ CTs burden. The conventional hardwire communication between CTs and protective relays has imposed difficulties in selecting the best possible protective relay devices to be used with the intended CTs so as not to overburden and saturate the CTs. Any saturation on the part of the CTs will incur errors on the measurements and tripping decisions made by the protective relays. In order to address this problem, a study has been carried out to evaluate the performance of a wireless differential transformer protection using Wireless Fidelity (Wi-Fi) that has done away with the traditionally hardwired copper communication medium of incoming measured voltages and currents of relay from the CTs. This approach is envisaged to be able to minimize the CT burden due the absence of signaling copper cables, reduce CT saturation and, importantly, performs a reliable protection system of the differential protective relay. The works involved are simulating transformer power quantities and wireless transmitted signals using the National Instrument data acquisition device (NI-DAQ) NI 9227 and modelling a transformer differential protection using National Instrument graphical programming tool LabVIEW. The results from the experiment demonstrate that the wireless transformer differential protection is able to avoid CT overburdening and saturation and, hence allow a more efficient protection operation performed by the relay. The fact that it is wireless, the cost of implementation can also be reduced and the problems of electromagnetic interference can be minimized.